Implikasi Ideologi Terhadap Strategi Penterjemahan Unsur Budaya dalam Siri Harry Potter ke dalam Bahasa Melayu Ideological Implication on the Strategy for Translating Cultural Elements in the Harry Potter Series into Malay (KEMANUSIAAN The Asian Journal of Humanities, 2019)
Translators make deliberate choices when deciding translation strategies. The choices, among others, are based upon the extent of power the translators have for decision-making. The choice of translation strategy also reflects upon the status of a source text compared to translated text, as well as the ideological motivation guiding translation activities at a given time. The tendency in the strategy used by a translator, whether source or text-oriented, can be determined by investigating how culture-specific items are translated. Thus, this study has been carried out to identify the strategy used to translate a phenomenon in modern children’s literature that is the Harry Potter book series, and to analyse the ideological and power factors that influenced the choice of strategy. Eighty-four culture-specific items have been identified and grouped according to Aixela’s (1996) classification of culture-specific items. The procedures and overall strategy were based on the translation procedures classification model by Qafzezi (2013) which leverages the typology of procedures for translating culture-specific items by Ivir (1987) and Venuti’s (2008) framework for translation strategies. The findings show that the translation strategy used to translate the Harry Potter series into Malay is largely source-oriented. The translator has limited power in deciding the strategy for translating the book series. The study also indicates that there has been a change in the ideological aspect behind children’s literature translation activities in Malaysia now compared to the period of post-colonialism in the 1970s and 1980s. Penterjemah lazimnya membuat pemilihan terancang dalam proses menentukan strategi penterjemahan. Pemilihan ini antara lain bergantung kepada sejauh mana kuasa yang diberikan kepada mereka untuk membuat keputusan. Pemilihan strategi penterjemahan juga mencerminkan status teks asal berbanding teks sasaran serta ideologi yang mendorong kegiatan penterjemahan pada satu-satu masa tertentu. Kecenderungan strategi yang digunakan oleh penterjemah sama ada berorientasikan sumber atau sasaran boleh ditentukan dengan mengkaji cara sesuatu unsur budaya diterjemahkan. Sehubungan itu, kajian ini dijalankan bagi mengenal pasti strategi yang digunakan untuk menterjemah karya sastera kanak-kanak yang menjadi fenomena iaitu siri Harry Potter serta menganalisis faktor ideologi dan kuasa yang mendorong pemilihan strategi tersebut. Sebanyak 84 unsur budaya telah dikenal pasti dan dikelaskan berdasarkan klasifikasi unsur budaya oleh Aixela (1996). Prosedur dan strategi keseluruhan penterjemahan dibuat berdasarkan model klasifikasi pendekatan penterjemahan oleh Qafzezi (2013) yang memanfaatkan prosedur penterjemahan unsur budaya oleh Ivir (1987) dan strategi penterjemahan oleh Venuti (2008). Analisis kajian menunjukkan bahawa strategi penterjemahan yang digunakan untuk menterjemah siri Harry Potter ke dalam bahasa Melayu lebih cenderung kepada berorientasikan sumber. Penterjemah didapati memiliki kuasa yang terhad dalam menentukan strategi penterjemahan yang digunakan. Kajian ini juga mendapati bahawa telah berlaku perubahan ideologi dalam aktiviti penterjemahan karya sastera kanak-kanak di Malaysia pada masa kini dibandingkan dengan tempoh semasa pasca penjajahan.